Alginate coarse/nanoemulsions containing Zataria multiflora Boiss essential oil as edible coatings and the impact on microbial quality of trout fillet. (6th January 2020) - Khanzadi, Saeid; Keykhosravy, Kobra; Hashemi, Mohammad; Azizzadeh, Mohammad
Abstract: In this study, the effect of edible coarse/nanoemulsions of alginate as coating containing Zataria multiflora Boiss essential oil (ZEO) on the microbial quality of fish fillets was investigated at three concentrations (i.e. 0.25%, 0.5% and 1% [w/v]) in 16 days of storage at 4°C. Moreover, a comparison was made between the fabricated coarse emulsion and nanoemulsion coatings by particle size and polydispersity index analyses. Sample analysis was performed with regard to total viable count (TVC), total psychrophilic count (TPC), hydrogen sulphide‐producing bacteria count (HSC) and Enterobacteriaceae count (ENC) on days 0, 4, 8, 12 and 16. According to the findings, all the samples showed increased microbial counts during the storage periods. The highest reduction rates of TVC (about 2 log CFU/g), TPC (about 1 log CFU/g), HSC (about 1.5 log CFU/g) and ENC (about 3 log CFU/g) were observed in the nanoemulsion of alginate containing 1% w/v ZEO (NE 1%) samples, compared with alginate and control samples. The microbial growth was significantly inhibited in all treatments, compared with that in the control ( p  < .05). Accordingly, it can be concluded that nanoemulsion coating was more effective than coarse emulsion to prolong the durability of fish fillets and revealed a faster and greater inhibition of microbial flora, compared with coarse emulsions during the storage time.